Analysis of Online Transportation User Satisfaction Using the Customer Satisfaction Index (CSI) and Important Performance Analysis (IPA) Methods In Palembang City - Merry Agustina; Vivi Sahfitri; Triani Astuti (Universitas Bina Darma, 2022)
The development of Information Technology today has brought many changes in various fields of human life. One of them is the field of transportation services. The existence of online transportation is slowly shifting the use of conventional public transportation. Online Transportation is a transportation service that utilizes network technology, which is based on the internet network in carrying out all its transaction activities. The increasing number of users of online transportation services is an option for the public to use these services based on satisfaction with the services provided to their customers. This study aims to determine the level of satisfaction of online transportation users using the Customer Satisfaction Index (CSI) Method and the Importance Performance Analysis (IPA) method. The results showed that the level of user satisfaction measured by the CSI method showed a satisfaction index of 0.7728 or 77.28%, which means that the satisfaction index value of online transportation users is on the criteria of